Comparison of pharmacokinetics and safety between CE-fosphenytoin sodium, fosphenytoin sodium, and phenytoin sodium after intravenous and intramuscular administration in healthy volunteers - Li, Xiaojiao; Wu, Min; Sun, Jixuan; Jin, Weili; Han, Lei; Xu, Jia; Liu, Jingrui; Zhang, Hong; Wang, Jing; Wang, Daidi; Zhang, Hanyi; Zhang, Qing; et al. (Frontiers in Pharmacology, 2023)
Abstract Background: Captisol® Enabled-fosphenytoin sodium (CE-fosphenytoin sodium) injection is a modified formulation of fosphenytoin sodium. Objective: We aim to compare the intravenous and intramuscular bioavailability and safety between CE-fosphenytoin sodium, fosphenytoin sodium (Cerebyx®), and phenytoin sodium (intravenous injection only). Methods: In pivotal study 1, 54 subjects were divided into three sequence groups to receive intravenous injection with 250 mg of phenytoin sodium equivalent (PE) CE-fosphenytoin sodium (T) or fosphenytoin sodium (R1), 250 mg of phenytoin sodium (R2) in period 1. After 14 days washout period, 36 subjects were randomized to two treatment sequence groups (T-R1 or R1-T, n=18 per group) in period 2, in which the subjects who received R2 in period 1 were removed, those received T in period 1 used R1 (T-R1), while those previously received R1 used T (R1-T). In pivotal study 2, a single intramuscular dose of T (400 mg PE) or R1 (400 mg PE) was administrated, according to the individual sequential treatment assignment in each period. There was a washout (14 days) before receiving the next period study drug. Results: T and R1 have similar pharmacokinetic characteristics regarding total and free phenyotoin, showing bioequivalence of both drugs in the intravenous and intramuscular administration. The geometric mean ratio was close to 1 (0.98-1.06). The AUC of total and free phenytoin in those intravenously received T and R1 was very similar to those received R2, although their Cmax was lower than subjects with R2. Overall, treatment with T and R1 was safe and well tolerated, without serious adverse event (SAE) or grade III adverse events (AEs). With intravenous or intramuscular treatment, the incidence of drug-related AEs using T was similar with R1. Treatment with T and R1 had clearly superior tolerability than R2. Conclusions: CE-fosphenytoin sodium is a promising substitute for fosphenytoin sodium.